Nitrogen enriched biochar used as CO2 adsorbents: a brief review - Yuanting Qiao; Chunfei Wu (Carbon Capture Science & Technology, 2022)
It is widely acknowledged that the increasing CO2 concentration has led to the rise of temperature in the earth. Thus, capturing CO2 to alleviate environmental catastrophic is becoming important and urgent. Among the CO2 sorbents reported, solid adsorbents are advantageous in CO2 adsorption, CO2/N2 selectivity, easy operation and good regeneration ability. Biochar-based sorbents are promising for CO2 capture because they are self-sufficient in energy requirements, wide availability, renewability, low cost, and high porous structure. In addition, N-containing functional groups are used to improve the capability of CO2 adsorption of biochar. This review aims to evaluate the preparation and performance of nitrogen-enriched biochar for CO2 capture. Throughout this review paper, the current N-containing precursors and biomass, as well as the technologies for the preparation of N-rich biochar are discussed. It is concluded that cheaper and more sustainable ways should be proceeded to produce N-rich biochar in the field of CO2 capture research.